Who cooks the books in China, and does it pay? Evidence from private, high‐technology firms - Stuart, Toby; Wang, Yanbo (Strategic Management Journal, 2016)
Research summary: We document the extent of fraudulent reporting among 467 private Chinese technology companies. Comparing the financial statements concurrently submitted to two different state agencies, we demonstrate a systematic gap in reported profit figures in the two sets of books. We find: (1) more than half the sampled companies report incentive‐compatible, materially discrepant profit numbers to the two agencies; (2) politically connected companies are approximately 18 percent more likely to commit fraud and those with venture capital backing are 19 percent more likely to do so; and (3) it pays to cheat. We estimate that companies who “cook” their books have considerably higher odds of receiving an innovation grant. Especially given its prevalence, we conclude that fraud can be a source of performance differential for emerging market companies . Managerial summary: We document that more than half of a sample of 467 private, Chinese technology companies engage in fraudulent financial reporting. By comparing the financial statements companies concurrently submitted to two different state agencies, we demonstrate a systematic gap in reported profit figures in the two sets of books. Relative to the companies without these attributes, we find that politically connected companies are approximately 18 percent more likely to commit fraud and those with venture capital backing are 19 percent more likely to do so. Furthermore, we show that it pays to cheat. We estimate that companies who “cook” their books have considerably higher odds of receiving a government‐sponsored innovation grant. Therefore, fraud can be a source of performance differential for emerging market companies . Copyright © 2015 John Wiley & Sons, Ltd.